Analysis of digital technology applications for consumer price monitoring in Uzbekistan - Ziyamatov Bekzod Yoqub o’g’li (Цифровые модели и решения)
The article aims to analise the current state of digital technologies and prospects of their introduction into the economy of Uzbekistan for monitoring consumer prices in the country. The paper highlights the main problems that are associated with the use of digital technology to monitor consumer prices, and suggests ways to solve them. The evidence of the study comes from scientific publications, analytical materials and regulatory documents of Uzbekistan. The work relies on analysing the impact of digitalisation on monitoring infla tionary processes, including methods for ensuring data integration, increasing transparency and management efficiency. According to the findings, the author presents recommenda tions for the development of digital infrastructure, which include advanced training of per sonnel, strengthening cybersecurity, and increasing the accessibility of digital platforms to the public. The study concludes that digital technology is significant as a factor in ensuring sustainable economic growth and price stability.